Pengaruh Harga, Kualitas Pelayanan, Fasilitas, Kepercayaan dan Citra Merek Terhadap Keputusan Pembelian Tiket Kereta Api Indonesia (Studi Kasus Mahasiswa Domisili Kota Malang) - Ulayya, Afifah Azizah; Arifin, Rois; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The rapid development of train transportation services in Indonesia presents challenges and opportunities for PT Kereta Api Indonesia to improve consumer purchasing decisions, especially among students. This study aims to determine and analyze whether the variables of price, service quality, facilities, trust, and brand image significantly influence consumer decisions in purchasing train tickets. This study uses a survey method by distributing quisioren to respondent. This research uses a quantitative approach to determine and analyze the influence between variables. Maholtra’s theory is used in sampling, namely the number of question items x 5 so that the number of samples set is 120 samples. This study uses Validity test, reliability test, Normality test, multicollinearity test, heteroscedasticity test, autocorrelation, multiple linear analysis test, F test, t test and coefficient of determination. This study uses SPSS 25 analysis tools, The results showed that the price variable has a significant influence on purchasing decisions, as well as service quality which also has a significant influence on purchasing decisions. facilities had a significant effect on purchasing decisions. Trust has a significant effect on purchasing decisions, and brand image has a significant effect on purchasing decisions. There is also a simultaneous influence on the variables of price, service quality, facilities, trust and brand image on purchasing decisions for train tickets for students domiciled in Malang City. Keywords: Price, Service Quality, Facilities, Trust, Brand Image, Purchasing Decision, Ticket KAI.